280 Distraction therapy for pain and anxiety in paediatric patients in the prehospital setting, a systematic review. (1st May 2022) - Robinson, T; Delorenzo, A; Howell, S; Cameron, P; Stock, A; Smith, K; Eastwood, K
Abstract : Background: Distraction therapies are widely used to manage pain and anxiety in paediatric emergency departments (ED). Paediatric patients also comprise up to 13% of some ambulance services workloads 1 yet only a single study exists outlining the ad-hoc use of paramedic-initiated distraction therapy. 2 Building rapport with frightened, unwell children is challenging for paramedics, but is essential to facilitate rapid assessment and care. 1, 3 .This review aims to identify effective ED distraction techniques potentially suitable for use in paediatric patients in the prehospital setting. Method: Databases and grey literature sources including Ovid Medline, EMBASE and CINAHL and Google Scholar were searched from their beginning to October 2021. English language interventional or observational studies were included if they reported on distraction techniques suitable for use in the prehospital setting, paediatric ED presentations, and pain and/or anxiety. Results: Of the 4, 054 records screened, 27 met the eligibility criteria. Twenty randomised trials and seven interventional studies involved children aged three months to 18 years. Distraction techniques were digital, non-digital and environmental adaptations and included virtual-reality, cartoons, music, vibration devices, bubble-blowing and ambient lighting. Ten studies reported significant reductions in self-reported pain and seven for self-reported anxiety. Some reported reduced pharmacological administration and improved patient cooperation, and parent and/or healthcare provider satisfaction when using distraction. Studies were highly heterogeneous with 17 distractors and 21 pain and/or anxiety measurement tools used. Conclusion: A range of effective distraction techniques exist in paediatric EDs that may be suitable for the prehospital setting to manage pain and/or anxiety and improve patient outcomes. References: Fowler J, Beovich B, Williams B. Improving paramedic confidence with paediatric patients: a scoping review. Australasian Journal of Paramedicine 2017;15 (1). Preston C and Bray L. Developing understanding and awareness of children's distress, distraction techniques and holding. Journal of Paramedic Practice 2015;7 (3):122–130. Cushman JT, Fairbanks RJ, O'Gara KG, et al . Ambulance personnel perceptions of near misses and adverse events in pediatric patients. Prehosp Emerg Care 2010;14 :477–84. Conflict of interest: None. Funding: AU$4000 in funding has been provided by the Australia and New Zealand College of Paramedicine, and AU$11, 000 in funding was provided through a Monash University Advancing Womens Research Success Grant for this program of research. Dr Eastwood, Dr Howell and Professor Cameron are supported by the National Health and Medical Research Council (NHMRC) Prehospital Emergency Care Centre for Research Excellence (PEC-ANZ; #1116453).